Commitment to Aerobic Glycolysis Sustains Immunosuppression of Human Mesenchymal Stem Cells. (1st October 2018) - Liu, Yijun; Yuan, Xuegang; Muñoz, Nathalie; Logan, Timothy M.; Ma, Teng
Abstract: Human mesenchymal stem cells (hMSCs) promote endogenous tissue repair in part by coordinating multiple components of the host immune system in response to environmental stimuli. Recent studies have shown that hMSCs are metabolically heterogeneous and actively reconfigure metabolism to support the biochemical demands of tissue repair. However, how hMSCs regulate their energy metabolism to support their immunomodulatory properties is largely unknown. This study investigates hMSC metabolic reconfiguration during immune activation and provides evidence that the hMSC metabolic state significantly influences their immunomodulatory properties. Specifically, hMSC immune polarization by interferon-gamma (IFN-γ) treatment leads to remodeling of hMSC metabolic pathways toward glycolysis, which is required to sustain the secretion of immunosuppressive factors. IFN-γ exposure also inhibited mitochondrial electron transport activity, and the accumulation of mitochondrial reactive oxygen species plays an important signaling role in this metabolic reconfiguration. The results also show that activation of the Akt/mTOR signaling pathway is required for metabolic reconfiguration during immune polarization and that interruption of these metabolic changes alters the immune response in IFN-γ licensed hMSCs. The results demonstrate the potential of altering hMSC metabolism to enhance their immunomodulatory properties and therapeutic efficacy in various diseases. Stem Cells Translational Medicine   2019;8:93–106 Abstract : hMSC immune polarization by IFN-γ leads to hMSC metabolic reconfiguration toward glycolysis, and inhibition of mitochondrial electron transport activity and the accumulation of mitochondrial reactive oxygen species (mROS) which further regulates IDO activation. Increased aerobic glycolysis is required to sustain the secretion of immunosuppressive factors and inhibition of T-cell proliferation. Activation of Akt/mTOR signaling pathway plays a central in metabolic reconfiguration during immune activation